Silane surface modified nanocellulose and rubber composition containing the same
Patent Information
- Application Number
- KR1020250205233
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2025-12-19
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2045-12-19
Smart Images

Figure 112025144480518-PAT00024_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to silane surface-modified nanocellulose and a rubber composition containing the same. Background Technology
[0002] Cellulose is attracting significant attention as a material capable of replacing or reinforcing inorganic fillers in the field of high-performance eco-friendly rubber composites, due to its eco-friendly nature as a natural polymer and its excellent mechanical strength. These cellulose materials offer potential applications in various fields, including automotive parts, tires, anti-vibration components, hoses, and seals. Securing high-performance composite material technology utilizing natural cellulose is also crucial to respond to global regulations requiring the use of sustainable materials.
[0003] However, cellulose presents a problem in that it exhibits very strong hydrophilic properties due to its structural presence of a large number of hydroxyl groups (-OH) on its surface. Because of this strong hydrophilicity, cellulose has significantly low compatibility with rubber matrices, which are inherently non-polar materials. When compatibility is low, it is difficult for cellulose to be uniformly dispersed within the rubber during the manufacture of composite materials, which is a major factor limiting its use as a rubber reinforcing filler.
[0004] In conventional technology, surface modification techniques using silane-based coupling agents were applied to address the compatibility issues between the hydrophilicity of cellulose and the rubber matrix. While existing silane modification techniques focused on improving dispersibility within the rubber by controlling hydrophobicity through the formation of siloxane bonds on the cellulose surface, these techniques still suffered from a fundamental problem in that they failed to induce chemical bonding with the rubber matrix. Consequently, there are limitations in maximizing interfacial adhesion between the cellulose filler and the rubber matrix due to the lack of chemical bonding. Therefore, it is difficult to significantly improve the mechanical properties of rubber composites, such as wear resistance, tensile strength, and fatigue life, to desired levels using conventional technology.
[0005] Therefore, there is an urgent need for research on nanocellulose and rubber compositions for rubber reinforcement that can simultaneously improve dispersibility, wear resistance, and mechanical properties of rubber. The problem to be solved
[0006] To solve the aforementioned problems, the present invention aims to provide a rubber-reinforcing nanocellulose capable of securing dispersibility through cellulose surface modification while simultaneously maximizing interfacial adhesion by directly forming chemical bonds with rubber chains during the vulcanization process, a rubber composition containing the same, and a method for manufacturing the same.
[0007] In addition, another objective of the present invention is to provide a rubber composite material in which nanocellulose is dispersed through chemical bonding within a rubber matrix, and a method for manufacturing the same. means of solving the problem
[0008] In order to achieve the aforementioned objectives, the inventors continuously researched to manufacture nanocellulose capable of simultaneously improving dispersibility and the mechanical properties of rubber. As a result, they discovered that when nanocellulose satisfying a specific aspect ratio and degree of crystallinity is surface-modified with a double-bond-containing silane surface modifier, not only is dispersibility with rubber improved by controlling the degree of hydrophobicity, but interfacial adhesion is maximized by directly forming chemical bonds with rubber chains during the vulcanization process, thereby enabling the production of a rubber composite material with excellent mechanical strength, thus completing the present invention.
[0009] The present invention provides a rubber composition comprising nanocellulose and raw rubber containing a structure represented by the following chemical formula 1 at the terminal end.
[0010] [Chemical Formula 1]
[0011]
[0012] In the above chemical formula 1,
[0013] R1 and R2 are independently hydrogen, hydroxy, alkyl, or alkoxy, and
[0014] L is a direct bond or an alkylene, and
[0015] X is a vinyl group or a (matte)acrylic group, and
[0016] * is a connector.
[0017] According to one embodiment, the rubber-reinforcing nanocellulose may contain one or more selected from the group consisting of a first repeating unit represented by the following chemical formula 2, a second repeating unit represented by the following chemical formula 3, and a third repeating unit represented by the following chemical formula 4.
[0018] [Chemical Formula 2]
[0019]
[0020] [Chemical Formula 3]
[0021]
[0022] [Chemical Formula 4]
[0023]
[0024] In the above chemical formulas 2 to 4,
[0025] R1 to R6 are independently hydrogen, hydroxy, alkyl, or alkoxy, and
[0026] L1 to L3 are independently directly bonded or alkylenes, and
[0027] X is a vinyl group or a (matte)acrylic group.
[0028] According to one embodiment, the nanocellulose for rubber reinforcement may have an average diameter of 1 to 10 nm and an average aspect ratio of 150 or more.
[0029] According to one embodiment, the nanocellulose for rubber reinforcement may have a crystallinity of 70% or more as analyzed by XRD.
[0030] According to one embodiment, the nanocellulose for rubber reinforcement may have a degree of substitution of 0.7 to 2.0 mmol / g.
[0031] According to one embodiment, the rubber-reinforcing nanocellulose may contain 1 to 10 atoms of Si elements relative to the total elements.
[0032] According to one embodiment, the nanocellulose for rubber reinforcement may be manufactured from cotton linters.
[0033] According to one embodiment, the nanocellulose for rubber reinforcement may be included in an amount of 1 to 50 parts by weight per 100 parts by weight of raw rubber.
[0034] According to one embodiment, the raw rubber may include natural rubber, synthetic rubber, or a mixed rubber in which natural rubber and synthetic rubber are mixed.
[0035] According to one embodiment, the raw rubber may comprise one or more selected from the group consisting of styrene butadiene rubber, butadiene rubber, butyl rubber, halogenated butyl rubber, styrene butadiene rubber containing isoprene, styrene butadiene rubber containing nitrile, and neoprene rubber.
[0036] The present invention can provide a nanocellulose for rubber reinforcement that contains a structure represented by the following chemical formula 1 at the ends, has a crystallinity of 70% or more as analyzed by XRD, has an average diameter of 1 to 10 nm, and an average aspect ratio of 150 or more.
[0037] [Chemical Formula 1]
[0038]
[0039] In the above chemical formula 1,
[0040] R1 and R2 are independently hydrogen, hydroxy, alkyl, or alkoxy, and
[0041] L is a direct bond or an alkylene, and
[0042] X is a vinyl group or a (matte)acrylic group, and
[0043] * is a connector.
[0044] According to one embodiment, the rubber-reinforcing nanocellulose may contain one or more selected from the group consisting of a first repeating unit represented by the following chemical formula 2, a second repeating unit represented by the following chemical formula 3, and a third repeating unit represented by the following chemical formula 4.
[0045] [Chemical Formula 2]
[0046]
[0047] [Chemical Formula 3]
[0048]
[0049] [Chemical Formula 4]
[0050]
[0051] In the above chemical formulas 2 to 4,
[0052] R1 to R6 are independently hydrogen, hydroxy, alkyl, or alkoxy, and
[0053] L1 to L3 are independently directly bonded or alkylenes, and
[0054] X is a vinyl group or a (matte)acrylic group.
[0055] According to one embodiment, the rubber-reinforcing nanocellulose may contain 1 to 10 atoms of Si elements relative to the total elements.
[0056] According to one embodiment, the rubber-reinforcing nanocellulose may be prepared by defibrating enzyme-pretreated cotton linters.
[0057] The present invention can provide a rubber composite material manufactured by vulcanizing the aforementioned rubber composition, wherein nanocellulose is dispersed within a rubber matrix and the rubber reinforcing nanocellulose is chemically bonded to the rubber matrix. Effects of the invention
[0058] The rubber composition comprising the rubber-reinforcing nanocellulose of the present invention can maximize interfacial adhesion, increase dispersion stability, and improve stress transfer efficiency by inducing the formation of chemical bonds between rubber and cellulose through the formation of double bonds at the ends of the rubber matrix during the vulcanization process by incorporating the rubber-reinforcing cellulose into the rubber. A rubber composite material manufactured from the above rubber composition can improve mechanical properties such as wear resistance, tensile strength, elongation at break, and fatigue life.
[0059] In addition, the nanocellulose for rubber reinforcement of the present invention can partially replace inorganic fillers such as silica and carbon black that were previously used, thereby ensuring lightweighting and eco-friendliness. Furthermore, since the manufacturing method of the nanocellulose for rubber reinforcement can be carried out at a low temperature under alcohol-water conditions, it has the advantage of being highly compatible with existing rubber mixing and vulcanization processes and is stable, allowing for mass production. Brief explanation of the drawing
[0060] Figure 1 is the FT-IR spectrum of nanocellulose according to Preparation Example 1 and Example 1. Figure 2 shows the contact angle measurement results of nanocellulose according to Preparation Example 1 and Example 1. Specific details for implementing the invention
[0061] Unless otherwise defined in this specification, all technical and scientific terms have the same meaning as generally understood by those skilled in the art to which the present invention pertains. The terms used in the description herein are merely for the purpose of effectively describing specific embodiments and are not intended to limit the present invention.
[0062] The singular form used in this specification is intended to include the plural form unless specifically indicated otherwise in the context.
[0063] Additionally, numerical ranges used herein include lower and upper limits and all values within the range, increments logically derived from the form and width of the defined range, all of which are limited values, and all possible combinations of upper and lower limits of numerical ranges defined in different forms. Unless otherwise specifically defined in this specification, values outside the numerical range that may occur due to experimental error or rounding are also included in the defined numerical range.
[0064] Additionally, units used herein without special mention are based on weight, for example, units of % or ratio mean weight % or weight ratio, and weight % means the weight percentage of any one component of the total composition that occupies the composition, unless otherwise defined.
[0065] The term “comprising” in this specification is an open description having an equivalent meaning to expressions such as “comprising,” “containing,” “having,” or “characterizing,” and does not exclude elements, materials, or processes not additionally listed.
[0066] Additionally, the term "substituted" in this specification means that a hydrogen atom of the substituted portion (e.g., alkyl, alkylene, aromatic ring, alicyclic ring, heterocyclic ring, etc.) is replaced by a substituent. Unless otherwise specified regarding substituents, any substituent of the present invention may be hydroxy, halogen, nitro, cyano, amino, carboxyl, carboxylate, C 1-10 Alkyl, C 1-10 Alkenyl, C 1-10 Haloalkyl, C 1-10 Alkoxy, C 1-10 Alkoxycarbonyl, C 3-20 Cycloalkyl, C 6-20 Aril C 1-10 Alkyl, C 6-20 Aryl and C 3-20 Includes heteroaryls, etc.
[0067] Hereinafter, a nanocellulose for rubber reinforcement and a rubber composition containing the same according to one embodiment of the present invention will be described in more detail.
[0068] The present invention may provide surface-modified nanocellulose for rubber reinforcement. The nanocellulose for rubber reinforcement may be one in which one or more hydroxyl groups of the cellulose structure are substituted with a substituent containing a double bond, i.e., an alkenyl group, and the nanocellulose for rubber reinforcement may be prepared by reacting nanocellulose with a silane compound containing an alkenyl group.
[0069] According to one embodiment, the rubber-reinforcing nanocellulose may contain a structure represented by the following chemical formula 1 at the end.
[0070] [Chemical Formula 1]
[0071]
[0072] In the above Chemical Formula 1, R1 and R2 are independently hydrogen, hydroxyl, alkyl, or alkoxy, L is a direct bond or alkylene, X is a vinyl group or (meth)acrylic group, and * is a linker. In this case, one or more carbons of the alkylene may optionally be substituted with -C(=O)O-, -C(=O)-, -OC(=O)-, or -O-. Additionally, the (meth)acrylic group may include both acrylic and methacrylic groups.
[0073] Specifically, in the above chemical formula 1, R1 and R2 are independently C 1-10 alkyl or C 1-10 It is an alkoxy, and L is directly bonded or C 1-10 It is an alkylene, and X can be a vinyl group or a (meth)acrylic group. Or R1 and R2 are independently C 1-5 alkyl or C 1-5 It is an alkoxy, and L is directly bonded or C 1-5 It is an alkylene, and X can be a vinyl group or a (meth)acrylic group.
[0074] According to one embodiment, the nanocellulose for rubber reinforcement may contain one or more selected from the group consisting of a first repeating unit represented by the following chemical formula 2, a second repeating unit represented by the following chemical formula 3, and a third repeating unit represented by the following chemical formula 4. Preferably, the nanocellulose for rubber reinforcement may include all of the first repeating unit, the second repeating unit, and the third repeating unit.
[0075] [Chemical Formula 2]
[0076]
[0077] [Chemical Formula 3]
[0078]
[0079] [Chemical Formula 4]
[0080]
[0081] In the above chemical formulas 2 to 4, R1 to R6 are independently hydrogen, hydroxyl, alkyl, or alkoxy, L1 to L3 are independently direct bonds or alkylenes, and X is a vinyl group or a (meth)acrylic group. In this case, one or more carbons of the alkylene may optionally be substituted with -C(=O)O-, -C(=O)-, -OC(=O)-, or -O-. Additionally, the (meth)acrylic group may include both an acrylic group and a methacrylic group.
[0082] Specifically, in the above chemical formulas 2 to 4, R1 to R6 are independently C 1-10 alkyl or C 1-10 It is an alkoxy, and L1 to L3 are independently directly bonded to each other or C 1-10 It is an alkylene, and X may be a vinyl group or a (meth)acrylic group. Or R1 to R6 are independently C 1-5 alkyl or C 1-5 It is an alkoxy, and L1 to L3 are independently directly bonded to each other or C 1-5It is an alkylene, and X may be a vinyl group or a (meth)acrylic group. Or R1 to R6 are independently C 1-3 alkyl or C 1-3 It is an alkoxy, and L1 to L3 are independently directly bonded to each other or C 2-4 It is an alkylene, and X can be a vinyl group or a (meth)acrylic group.
[0083] According to one embodiment, the nanocellulose for rubber reinforcement may be produced from biomass according to a commonly used or known method. The biomass may include wood or non-wood, for example, the wood may include coniferous trees (softwood) such as pine, fir, larch, etc. and deciduous trees (hardwood) such as eucalyptus, poplar, birch, etc., and the non-wood may include cotton, rice straw, wheat straw, reeds, bagasse, bamboo, kenaf, papyrus, flax, esparto, jute, sabai, grass, hemp, corn stalks, banana leaves, jute, abaca, coir, pineapple, ramie, sisal, heneken, hemp, and rice husks.
[0084] The above-mentioned nanocellulose for rubber reinforcement may be prepared by subjecting the aforementioned biomass-derived pulp to physical pretreatment, chemical pretreatment, or physical / chemical pretreatment. The above-mentioned physical pretreatment may utilize physical treatment methods commonly used in the field of cellulose technology, and, for example, mechanical shear treatment may be performed using a grinder, a super mass colloider, an air-jet mill, an ultrasonic homogenizer, a high-pressure homogenizer, and a homo mixer, but is not limited thereto.
[0085] The above chemical pretreatment may use chemical treatment methods commonly used in the field of cellulose technology, for example, oxidation treatment using a TEMPO catalyst, and the nanocellulose produced accordingly may be a TEMPO-oxidized cellulose fiber. In addition, the physical / chemical pretreatment may involve performing both the physical pretreatment and the chemical pretreatment described above.
[0086] According to one embodiment, the nanocellulose for rubber reinforcement may be produced from cotton linters, specifically by defibrating enzyme-pretreated cotton linters. Through enzyme pretreatment, impurities in the raw material are removed to increase purity, and the fiber structure is softened and swollen, thereby enabling improved defibration efficiency and uniform nano-sizing in subsequent processes. Furthermore, the defibration may utilize conventional methods or known methods generally used for fiber defibration without limitation, and may, for example, use a grinder, a super mass collider, an air-jet mill, an ultrasonic homogenizer, a high-pressure homogenizer, and a homogenizer, but is not limited thereto.
[0087] According to one embodiment, the nanocellulose for rubber reinforcement has an average diameter of 1 to 20 nm, 1 to 10 nm, 1 to 7 nm, or 1 to 5 nm, an average length of 0.05 to 10 μm, 0.1 to 7 μm, or 0.5 to 5 μm, and an average aspect ratio of 50 or more, 100 or more, 150 or more, or 50 to 500, 100 to 400, or 150 to 400. Within the above range, a mechanical strength reinforcement effect and a dispersion effect within the matrix can be simultaneously achieved. If the aspect ratio is low, a mechanical strength reinforcement effect cannot be achieved, and if it is too high, the dispersion within the matrix may be reduced.
[0088] According to one embodiment, the nanocellulose for rubber reinforcement may have a crystallinity analyzed by XRD of 60% or more, 60 to 95%, 70% or more, 70 to 90%, or 75 to 85%. If the above range is satisfied, the rubber reinforcement effect can be improved.
[0089] According to one embodiment, the nanocellulose for rubber reinforcement may have some hydroxyl groups on its surface substituted with alkenyl groups, vinyl groups, or (meth)acrylic groups, and the degree of substitution is referred to as the degree of surface substitution, and the nanocellulose for rubber reinforcement may have a degree of substitution of 0.5 to 2.5 mmol / g, 0.7 to 2.0 mmol / g, or 1.0 to 1.8 mmol / g.
[0090] According to one embodiment, the nanocellulose for rubber reinforcement may contain 1 to 10 atomic percent, 1 to 5 atomic percent, 1 to 3 atomic percent, 1 to 2 atomic percent, or 1 to 1.5 atomic percent of Si (silicon) elements based on the total elements. The nanocellulose for rubber reinforcement may contain 1 to 15 wt percent, 1 to 10 wt percent, or 1 to 5 wt percent of Si (silicon) elements based on the total weight.
[0091] According to one embodiment, the nanocellulose for rubber reinforcement may contain 30 to 50 atomic percent, 35 to 45 atomic percent, or 40 to 43 atomic percent of O (oxygen) elements based on the total elements. The nanocellulose for rubber reinforcement may contain 30 to 60 wt%, 40 to 55 wt%, or 45 to 50 wt% of O (oxygen) elements based on the total weight.
[0092] According to one embodiment, the nanocellulose for rubber reinforcement may contain 40 to 70 atomic percent, 50 to 65 atomic percent, or 55 to 60 atomic percent of C (carbon) elements based on the total elements. The nanocellulose for rubber reinforcement may contain 35 to 70 wt%, 40 to 60 wt%, or 45 to 55 wt% of C (carbon) elements based on the total weight.
[0093] According to one embodiment, the nanocellulose for rubber reinforcement may be sheeted and have a contact angle of 40° or more, 45° or more, 50° or more, 55° or more, 60° or more, 65° or more, 70° or more, or 60 to 100°.
[0094] The present invention can provide a rubber composition comprising the aforementioned nanocellulose for rubber reinforcement and raw rubber. The rubber composition may further include additional additives typically added during the manufacture of the rubber composition.
[0095] According to one embodiment, the raw rubber may include natural rubber, synthetic rubber, or a mixed rubber in which natural rubber and synthetic rubber are mixed. The raw rubber may include one or more selected from the group consisting of styrene butadiene rubber, butadiene rubber, butyl rubber, halogenated butyl rubber, styrene butadiene rubber containing isoprene, styrene butadiene rubber containing nitrile, and neoprene rubber.
[0096] According to one embodiment, the nanocellulose for rubber reinforcement may be included in an amount of 1 to 50 parts by weight, 1 to 20 parts by weight, or 5 to 15 parts by weight per 100 parts by weight of raw rubber, but can be easily adjusted according to the desired physical properties and applications.
[0097] According to one embodiment, the additive may include one or more selected from the group consisting of inorganic fillers, dispersants, vulcanizing agents, vulcanization accelerators, activators, antioxidants, anti-aging agents, and softeners, but any material commonly used or known in the rubber industry may be used without limitation.
[0098] According to one embodiment, the inorganic filler may be an inorganic filler commonly used in rubber manufacturing or a commercially available product without limitation, and specifically, the inorganic filler may be a combination of one or more selected from carbon black, silica, etc.
[0099] According to one embodiment, the vulcanization accelerator may further include one or more combinations selected from the group consisting of thiazole-based (MBT, MBTS), sulfenamide-based (CBS, TBBS, DCBS), dithiocarbamate-based (ZDMC, ZDBC, ZDEC), thiuram-based (TMTD, TMTM), guanidine-based (DPG), dibenzimidazole (DIB), alkylphenol disulfide, ethylenethiourea, naphthylamine, meltone-based, etc.
[0100] According to one embodiment, the activator may use an organic peroxide or a metal oxide, and may further include one or more combinations selected from the group consisting of, for example, zinc oxide (ZnO), zinc carbonate, magnesium oxide (MgO), lead oxide, potassium hydroxide, stearic acid, zinc stearate, palmitic acid, linoleic acid, oleic acid, lauric acid, dibutyl ammonium oleate, and derivatives thereof.
[0101] The present invention can provide a rubber composite material manufactured by vulcanizing the aforementioned rubber composition, wherein nanocellulose is dispersed within a rubber matrix and the rubber reinforcing nanocellulose is chemically bonded to the rubber matrix. In one embodiment, the nanocellulose contains double bonds on its surface, allowing it to chemically bond to the rubber matrix during the vulcanization process, thereby possessing strong interfacial adhesion. This enables significantly improved dispersibility, strength reinforcement, and wear resistance.
[0102] Embodiments of the present invention will be described in detail below with reference to the attached drawings. However, this is provided to enable those skilled in the art to easily implement the invention, and the present invention may be embodied in various different forms, and the concept of the present invention is not necessarily limited to these embodiments.
[0103] [Physical Property Evaluation Methods]
[0104] 1) Average diameter and average length of nanocellulose: Nanocellulose diluted to 0.01 wt% was applied to the surface of MICA and dried, after which Z Height images were obtained in non-contact mode using an atomic force microscope (AFM). Based on the images, five random samples were selected to measure the diameter and length of the nanocellulose, and the average values of the remaining samples, excluding the maximum and minimum values, were calculated as the average diameter, average length, and average aspect ratio (length / diameter) of the nanocellulose.
[0105] 2) Degree of Crystallinity (XRD) [%]: After preparing nanocellulose as a powder or sheet, the degree of crystallinity was analyzed using an X-ray diffraction analyzer (XRD). In the case of the powder, it was prepared in the form of pellets for evaluation, and measurements were performed in the range of 2θ = 3° to 40° under Cu Kα radiation of 40 kV and 40 mA. From the X-ray diffraction spectrum obtained therefrom, the degree of crystallinity was calculated using the Segal method of [Equation 1] below.
[0106] [Equation 1] Degree of crystallization (%) = (I 200 - I amor ) / I 200 X 100)
[0107] (In the above Equation 1, I 200 is the maximum intensity (crystallization region) in the diffraction angle (2θ) 22±2° region, and I amor is the minimum intensity (amorphous region) in the diffraction angle (2θ) 18±2° region.
[0108] 3) Contact angle: After preparing nanocellulose into a sheet, the contact angle with respect to water was measured using a contact angle goniometer.
[0109] 4) Tensile properties: The tensile properties of rubber compositions or rubber composite materials were evaluated according to ASTM D412 (Standard Test Methods for Vulcanized Rubber and Thermoplastic Elastomers-Tension).
[0110] Tensile tests were performed using a Universal Testing Machine (Instron 3367). Test specimens were prepared according to ASTM D412 standards, and a load cell capacity of 500 N was used. The test was conducted at a tensile speed of 500 mm / min to obtain stress-strain curves. The initial grip distance of the specimens was set to 65 mm, and the elongation gauge length was set to 25 mm. The rubber reinforcement effect and improvement in material properties were evaluated using the tensile strength, elongation at break, and stress-strain curves obtained under these test conditions.
[0111] 5) Wear resistance: The wear characteristics of rubber compositions or rubber composite materials were measured according to the ISO 4649 test method. Under the conditions of a standard abrasive cloth (P240), a 10 N load, and a wear distance of 1000 m, the initial mass of the specimen (m0) and the mass of the specimen after wear (m) were measured. After calculating the volume using the respective densities (ρ0, ρ), the relative volume loss was calculated using Equation 2 below, and the lower the relative volume loss, the better the wear resistance of the corresponding material.
[0112] [Equation 2]
[0113]
[0114] In Equation 2 above, V0 is the volume of the initial test specimen (= m0 / ρ0), and V is the volume of the test specimen after wear (= m / ρ).
[0115] [Preparation Example 1]
[0116] 5 parts by weight of cotton lint (crystallization: 91%) was added to 100 parts by weight of distilled water to ensure the cotton lint was sufficiently submerged in the distilled water, and 3% by weight of purified cellulase was added to the distilled water. The mixture was then stirred at a speed of 100 rpm or less for 6 hours, while maintaining the temperature at 50℃. After stirring was completed, the mixture was left at a temperature of 25℃ for 1 day to perform a pretreatment process for cellulose decomposition.
[0117] Next, the enzyme-pretreated cotton lint was filtered, and a mixture was prepared to be contained in distilled water at a concentration of 1% by weight. The mixture was defibrated using a fiber refiner for 3 hours to obtain nanocellulose.
[0118] [Example 1]
[0119] Hydrogen chloride (HCl) was added to a composition containing 1 wt% of the nanocellulose of Preparation Example 1 and distilled water to adjust the pH to approximately 4. Subsequently, a silane solution containing 10 wt% vinyltrimethoxysilane in ethanol was added to the composition to satisfy 0.5 eq per AGU based on the silane equivalent, and the mixture was reacted for 1 hour at room temperature while stirring at 200 rpm. Then, sodium hydroxide was added to the composition to adjust the pH to approximately 10, and the mixture was reacted again for 5 hours at room temperature while stirring at 200 rpm. After the reaction was completed, the solid obtained by filtration was washed several times with distilled water and dried to obtain the nanocellulose according to Example 1.
[0120] According to Example 1, the average diameter of the nanocellulose was 3 nm, the average aspect ratio was 347, and the degree of crystallinity was measured to be 80%.
[0121] In addition, to confirm whether surface modification occurred, the Fourier transform infrared spectroscopy (FT-IR) spectra of the nanocellulose according to Preparation Example 1 and Example 1 were shown in Fig. 1, and silane modification was confirmed through changes in the peaks. Furthermore, the nanocellulose according to Preparation Example 1 and Example 1 was sheeted, and the contact angle with water was measured. As shown in Fig. 2, Preparation Example 1 showed 33.93˚ and Example 1 showed 73.29˚, confirming that they were hydrophobic.
[0122] In addition, the nanocellulose according to Preparation Example 1 and Example 1 was sheeted, and the elemental content of carbon (C), oxygen (O), and silicon (Si) was measured by EDS mapping based on field emission scanning electron microscope (FE-SEM) images, and the results are recorded in Table 1 below.
[0123] Carbon (C) Oxygen (O) Silicon (Si) atom% wt% atom% wt% atom% wt% Preparation Example 1 56.30 49.17 43.70 50.83 - - Example 1 57.20 49.53 41.52 47.89 1.28 2.59
[0124] [Example 2]
[0125] The above Example 1 was performed in the same manner as Example 1, except that triethoxyvinylsilane was used instead of vinyltrimethoxysilane.
[0126] [Example 3]
[0127] The above Example 1 was performed in the same manner as Example 1, except that 3-(trimethoxysilyl)propyl methacrylate was used instead of vinyltrimethoxysilane.
[0128] [Example 4]
[0129] The above Example 1 was performed in the same manner as Example 1, except that 3-(dimethoxy(methyl)silyl)propyl methacrylate was used instead of vinyltrimethoxysilane.
[0130] [Example 5]
[0131] The above Example 1 was performed in the same manner as Example 1, except that allyltrimethoxysilane was used instead of vinyltrimethoxysilane.
[0132] [Example 6]
[0133] 90 parts by weight of natural rubber latex and 10 parts by weight of nanocellulose prepared in Example 1 were added, and a rubber composition was prepared by stirring at 200 rpm at room temperature for 1 hour.
[0134] [Example 7]
[0135] 90 parts by weight of natural rubber latex and 10 parts by weight of nanocellulose prepared in Example 3 were added, and a rubber composition was prepared by stirring at 200 rpm at room temperature for 1 hour.
[0136] [Comparative Example 1]
[0137] The natural rubber latex used in Example 6 above was prepared.
[0138] [Comparative Example 2]
[0139] 90 parts by weight of natural rubber latex and 10 parts by weight of nanocellulose prepared in Preparation Example 1 were added, and a rubber composition was prepared by stirring at 200 rpm at room temperature for 1 hour.
[0140] [Evaluation Example 1]
[0141] A rubber composite material was prepared by drying the rubber composition of Example 6 at 70°C for 24 hours, and then molded into a sheet shape at 40°C using a Mixing Mill. Afterward, the tensile strength and elongation at break were measured according to the method described above, and the results were recorded in Table 2 below.
[0142] type Tensile strength (N / mm²) Break elongation (%) Comparative Example 1 0.16 311 Comparative Example 2 1.2 406 Example 6 1.6 333
[0143] As shown in Table 2 above, it was confirmed that the non-vulcanized rubber composite material prepared from the rubber composition of Example 6, which was prepared by mixing natural rubber latex and nanocellulose, showed significantly improved tensile strength and elongation at break compared to Comparative Example 1, which was pure natural rubber. In particular, Example 6 showed a 10-fold improvement in tensile strength compared to Comparative Example 1, confirming that a significant tensile strength reinforcement effect can be achieved solely through the addition of nanocellulose according to one example.
[0144] In addition, when comparing Comparative Example 2, which contains ordinary nanocellulose without silane surface modification, with Example 6, Example 6 showed a value approximately 25% higher than Comparative Example 2, confirming that the effect of improving tensile strength is achieved depending on the presence or absence of silane surface modification. Through this, it was confirmed that the silane surface-modified nanocellulose according to one embodiment can contribute to improving the mechanical properties of rubber by forming excellent interfacial interactions with the rubber matrix even before the vulcanization process.
[0145] [Evaluation Example 2]
[0146] The rubber composition of Example 8 was prepared by mixing 100 parts by weight of natural rubber latex, 10 parts by weight of the nanocellulose prepared in Example 1, 40 parts by weight of silica (SiO2), 20 parts by weight of carbon black, 2 parts by weight of a dispersant, 2 parts by weight of an activator (zinc oxide), 1 part by weight of a vulcanizing agent (sulfur), and 1.5 parts by weight of a vulcanization accelerator (TBBS), and uniformly kneading the mixture using a roll or a kneader. The prepared rubber composition was [subject to] 150~180 A rubber composite material was manufactured by performing a press vulcanization process for a set time (40 minutes) within the temperature range. As comparative examples, a rubber composite material was manufactured in Comparative Example 3, in which nanocellulose was not added to the rubber composition of Example 8, and in Comparative Example 4, in which nanocellulose from Preparation Example 1 was used instead of Example 1. The tensile strength, elongation, and wear resistance (amount of wear) of the manufactured rubber composite specimens were evaluated according to standards such as ASTM D412 and ISO 4649 and recorded in Table 3 below.
[0147] type Tensile strength (kgf / cm²) 2 ) Growth Rate (%) Wear resistance (mm) 3 ) Comparative Example 3 110 456 115 Comparative Example 4 142 491 186 Example 8 154 598 95
[0148] As shown in Table 3 above, in the case of the rubber composition according to one embodiment, it was confirmed that the reinforcing effect was significantly increased by the surface-modified nanocellulose forming chemical bonds within the rubber matrix during the vulcanization process. In particular, the nanocellulose surface-modified with double-bonded silane directly participated in the cross-linking network with the rubber chains during the vulcanization process and was dispersed by chemical bonding with the rubber matrix, thereby greatly improving interfacial adhesion. Consequently, it exhibited significantly improved tensile strength and wear resistance compared to Comparative Example 3, which contained only inorganic fillers such as silica and carbon black. Furthermore, by using unmodified nanocellulose under the same formulation conditions, it was confirmed that the rubber composition according to one embodiment formed an interaction-based hybrid reinforcing structure by exhibiting a higher reinforcement factor compared to Comparative Example 4.
[0149] As described above, the present invention has been explained by limited embodiments, but this is provided merely to aid in a more comprehensive understanding of the invention. The present invention is not limited to the above embodiments, and those skilled in the art can make various modifications and variations from this description.
[0150] Accordingly, the scope of the present invention is not limited to the described embodiments, and all things equivalent to or having equivalent variations to the claims set forth below, as well as the claims set forth below, shall be considered to fall within the scope of the concept of the present invention.
Claims
Claim 1 A rubber composition comprising nanocellulose for rubber reinforcement, raw rubber, a vulcanizing agent, and a vulcanization accelerator, wherein the nanocellulose for rubber reinforcement has a crystallinity of 70% or more as determined by XRD analysis, an average diameter of 1 to 10 nm, an average aspect ratio of 150 or more, and one or more hydroxyl groups of the cellulose structure are substituted with a structure represented by the following Chemical Formula 1 to be chemically bondable to the rubber matrix. [Chemical Formula 1] In the above chemical formula 1, R1 and R2 are independently hydrogen, hydroxy, alkyl, or alkoxy, L is a direct bond or alkylene, X is a vinyl group or (meth)acrylic group, and * is a linker. Claim 2 delete Claim 3 delete Claim 4 delete Claim 5 A rubber composition according to claim 1, wherein the nanocellulose for rubber reinforcement has a degree of substitution of 0.7 to 2.0 mmol / g. Claim 6 A rubber composition according to claim 1, wherein the nanocellulose for rubber reinforcement contains 1 to 10 atoms of Si elements based on the total elements. Claim 7 A rubber composition according to claim 1, wherein the nanocellulose for rubber reinforcement is manufactured from cotton linters. Claim 8 A rubber composition according to claim 1, wherein the rubber reinforcing nanocellulose is included in an amount of 1 to 50 parts by weight per 100 parts by weight of raw rubber. Claim 9 A rubber composition according to claim 1, wherein the raw rubber comprises natural rubber, synthetic rubber, or a mixed rubber in which natural rubber and synthetic rubber are mixed. Claim 10 A rubber composition according to claim 1, wherein the raw rubber comprises one or more selected from the group consisting of styrene butadiene rubber, butadiene rubber, butyl rubber, halogenated butyl rubber, styrene butadiene rubber containing isoprene, styrene butadiene rubber containing nitrile, and neoprene rubber. Claim 11 Nanocellulose for rubber reinforcement, wherein one or more hydroxyl groups of the cellulose structure are substituted with a structure represented by the following Chemical Formula 1 to enable chemical bonding with a rubber matrix, the degree of crystallization analyzed by XRD is 70% or more, the nanofibers have an average diameter of 1 to 10 nm, and the average aspect ratio is 150 or more. [Chemical Formula 1] In the above chemical formula 1, R1 and R2 are independently hydrogen, hydroxy, alkyl, or alkoxy, L is a direct bond or alkylene, X is a vinyl group or (meth)acrylic group, and * is a linker. Claim 12 delete Claim 13 In claim 11, the above-mentioned rubber-reinforcing nanocellulose comprises 1 to 10 atoms of Si elements based on the total elements. Claim 14 In claim 11, the above-mentioned nanocellulose for rubber reinforcement is a nanocellulose for rubber reinforcement manufactured by defibrating enzyme-pretreated cotton linters. Claim 15 A rubber composite material prepared by vulcanizing any one of the rubber compositions selected from claims 1, 5 to 10, wherein nanocellulose is dispersed within a rubber matrix, and the rubber reinforcing nanocellulose is chemically bonded to the rubber matrix by having one or more hydroxyl groups of the cellulose structure substituted with a structure represented by Chemical Formula 1.
Citation Information
Patent Citations
Tread Rubber Compound for Improving Braking Performance Using Modified-Cellulose and BIIR
KR1020170001246A
Surface modified cellulose nanofibrils
EP2196478A1
Resin composition obtained by blending modified cellulose fiber, and method for manufacturing modified cellulose fiber
JP2025069095A
Rubber composition for tire tread
KR100360940B1
Spinning machine having plural front top roller
KR100978531B1